UKACC International Conference on CONTROL 2010 2010
DOI: 10.1049/ic.2010.0416
|View full text |Cite
|
Sign up to set email alerts
|

Model Predictive Control for Energy and Leakage Management in Water Distribution Systems

Abstract: This paper considers development of a methodology for an on-line energy and leakage management in water distribution systems, formulated within a model predictive control framework. The approach involves calculation of control actions, i.e. time schedules for pumps, valves and sources, to minimize the costs associated with energy used for water pumping and treatment and water losses due to leakage, whilst satisfying all operational constraints. The process of computing the control action utilises EPAnet hydrau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The proposed method is based on formulating and solving an optimisation problem, similarly to Skworcow et al (2009bSkworcow et al ( , 2010. However, in this paper the considered network is of significantly higher complexity compared to our previous work, which required some changes to the modelling approach when the optimisation model is formulated, and resulted in a more general method applicable to a wider range of WDNs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed method is based on formulating and solving an optimisation problem, similarly to Skworcow et al (2009bSkworcow et al ( , 2010. However, in this paper the considered network is of significantly higher complexity compared to our previous work, which required some changes to the modelling approach when the optimisation model is formulated, and resulted in a more general method applicable to a wider range of WDNs.…”
Section: Methodsmentioning
confidence: 99%
“…EPANET input file (inp format), 2. EPANET binary simulation results file (bin format) produced by calling the simulator, 3. time-series files (csv format) describing initial schedules; when the scheduler is employed in an on-line receding-horizon environment (Skworcow et al, 2010), the schedules from the previous time step can be used as an initial condition for the current time step, 4. electricity tariffs (csv format),…”
Section: Methodsmentioning
confidence: 99%
“…Real-time control (RTC) of both types of UWC systems has received special attention during the last few years, due to the increasing demand for improved system performance to meet consumer and regulatory needs, often at reduced cost [5], [11]. The main goal to be achieved in DWNs is to reduce pumping costs -for instance, by filling tanks in low tariff periods -while maintaining adequate system pressure to meet fluctuating consumer demands [12]. Similarly, in urban drainage management, the goals are to minimize flooding and combined sewer overflow to the receiving environment (CSO) by controlling flow within the wastewater system, through for example, inline storage [13] or using underground detention tanks, gates and pumps [6], [14].…”
Section: Application Of Predictive Control Strategies To the Managemementioning
confidence: 99%
“…As discussed before, the behavior of some elements depends not only on their own state but also on that of other elements (for example weirs). Therefore, although the controloriented model of the SN can be represented, as in the case of DWNs, by a collection of expressions in (12) and (16), some tank inflows and/or outflows can show discontinuous dynamics. Several approaches have been derived for expressing this control-oriented model.…”
Section: Control-oriented Modelmentioning
confidence: 99%
“…In addition to the methods proposed for reduction in searching space, they showed that use of variable speed pumps can lead to more saving (about 10%) in pumping energy cost in comparison with fixedspeed pumps [17]. Also about pumps operation schedule in water distribution network we can point to the studies of Abdelmeguid (2010), Skworcow (2010), Fiorelli (2012) and Paluszczyszyn (2013) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%